Cutaneous amyloidosis in a patient with systemic amyloidosis due to multiple myeloma - Panagopoulos, Fotis; Jahaj, Edison; Papaodyssea, Ioanna; Stamatopoulos, Vasilis; Kounatidis, Dimitris; Vallianou, Natalia (Health & Research Journal, 2024)
Cutaneous manifestations in systemic amyloidosis secondary to multiple myeloma or AL amyloidosis are seen in approximately 15%-40% of patients with systemic amyloidosis. Cutaneous involvement has a preference for skin folds, retroauricular region, eyelids, neck and the axilla and may present in the form of purpura, domed papules or nodes resembling isolated nodular amyloidosis. Congo red staining remains the gold standard for diagnosis, revealing amyloid fibrils with apple-green birefringence in the polarized microscopy. It is noteworthy that patients may sometimes present with non-specific skin changes, suggestive of depositional disease, such as alopecia or nail dystrophy. Herein, we present a patient with systemic amyloidosis, who exhibited red-brown macules coalescing into a rippled pattern in the extremities, amyloid nodules in the peri-auricular region and dystrophic nails, findings that were attricuted to cutaneous amyloidosis in the context of systemic amyloidosis.